Cytomegalovirus encephalitis in an immunocompetent child: a sceptic diagnosis. (27th November 2012) - Belo, Filipa; Mendes, Isabel; Calha, Manuela; Mendonça, Carla
Abstract : The authors present the case of an apparently immunocompetent 9-year-old child with probable cytomegalovirus encephalitis. The clinical picture was characterised by fever, frontal headache and behavioural changes, associated with visual and auditory hallucinations. Cerebrospinal fluid (CSF) biochemistry and brain CT were normal. Electroencephalography showed left temporal paroxysmal activity. Diagnosis was based on cytomegalovirus (CMV) DNA detection on the CSF by PCR. Acyclovir and ceftriaxone were given until herpes simplex virus (HSV) and bacterial encephalitis were ruled out. Rapid resolution of fever and complete clinical recovery was observed. Remarkably, anti-CMV serum antibodies were not detected on admission or until 6 months later. This discrepancy led us to question the presence of an impaired specific host humoral response, immune evasion by the virus or a false-positive result for CMV DNA in CSF.